Impact of Longitudinal Virtual Primary Care on Diabetes Quality of Care. (20th August 2020) - Lu, A.; Gunzburger, E.; Glorioso, T.; Smith, W.; Whooley, M.; Ho, M.
Abstract : Individuals living in rural areas experience a higher prevalence of diabetes and diabetes‐related morbidity than their urban counterparts due to socioeconomic challenges and limited access to care. In randomized controlled trials, use of telemedicine has been effective in increasing access to care and lowering hemoglobin A1C levels for diabetic patients, but whether these results can be generalized to real‐world primary care settings remains unknown. We compare diabetes quality of care among veterans who received longitudinal virtual primary care versus those who received traditional in‐person care. The Virtual Integrated Multisite Patient Aligned Care Team (V‐IMPACT) is a novel primary care delivery model implemented by the Department of Veterans Affairs that utilizes video visits to provide longitudinal primary care services in rural areas that have difficulty recruiting and retaining primary care providers. We conducted a retrospective quasi‐experimental study utilizing difference‐in‐differences analysis to evaluate diabetes quality of care before and after implementation of V‐IMPACT in participating primary care clinics from January 1, 2016, through December 31, 2019, with staggered V‐IMPACT implementation across clinics occurring in 2018. Our primary outcome of interest was change in hemoglobin A1C (HbA1C) before and after implementation of V‐IMPACT among patients with diabetes. Secondary outcomes included the proportion who received urine microalbuminuria screening and were prescribed statins, ACE or ARBs. We identified 64 639 veterans with type 2 diabetes receiving care in 44 VA primary care clinics where V‐IMPACT was implemented. Patients were eligible for analysis if they had at least one primary care encounter and at least one documented hemoglobin A1C level available during the observation period. We excluded patients younger than 18 years old and those with metastatic cancer. Propensity score matching was used to construct a matched‐pair cohort of patients with balanced demographics and comorbidities who did and did not receive V‐IMPACT services. Our propensity‐matched cohort included 9150 veterans split evenly between those who participated in V‐IMPACT and those who remained in usual in‐person care. Mean HbA1C decreased from 7.35% to 7.29% among diabetics who were exposed to V‐IMPACT and from 7.29% to 7.23% among those receiving traditional in‐person care before and after V‐IMPACT implementation. No significant difference was found in the change in HbA1C between groups (difference‐in‐differences estimate, 0.0035%; −0.034 to 0.041%). We observed a 4.1% (95% CI 1.4‐6.8%) greater absolute increase in the proportion of diabetic Veterans prescribed statins in the V‐IMPACT group compared to the control group and a 5.7% greater increase in the proportion prescribed ACE/ARBs. V‐IMPACT implementation was not associated with significant changes in the proportion of veterans receiving urine microalbuminuria screening (−0.06%, 95% CI −2.9 to 2.8). The quality of diabetes care delivered by a longitudinal virtual primary care model was similar if not better than traditional in‐person care. Primary care access remains a challenge for many clinics and health systems serving rural populations. Our study demonstrates that a longitudinal telemedicine‐based primary care model can be effective for the management of diabetes and supports consideration of longitudinal telemedicine as a strategy to increase primary care access in rural communities. Department of Veterans Affairs.